Impact of high-dose statins on vitamin D levels and platelet function in patients with coronary artery disease. Issue 150 (February 2017) - Verdoia, Monica; Pergolini, Patrizia; Rolla, Roberta; Nardin, Matteo; Schaffer, Alon; Barbieri, Lucia; Daffara, Veronica; Marino, Paolo; Bellomo, Giorgio; Suryapranata, Harry; De Luca, Giuseppe; ,
Abstract: Background: Statins represent a pivotal treatment in coronary artery disease, offering a reduction in cardiovascular risk even beyond their lipid-lowering action. However, the mechanism of these "pleiotropic" benefits of statins is poorly understood. Vitamin D has been suggested as a potential mediator of the anti-inflammatory, anti-thrombotic and vascular protecting effects of statins. Aim of present study was to assess the impact of a high-intensity statin therapy on vitamin D levels and platelet function in patients with coronary artery disease. Methods: Patients discharged on dual antiplatelet therapy and high-intensity statins after an ACS or elective PCI were scheduled for main chemistry and vitamin D levels assessment at 30–90 days post-discharge. Vitamin D (25-OHD) dosing was performed by chemiluminescence method through the LIAISON® Vitamin D assay (Diasorin Inc). Platelet function was assessed by Multiplate® (multiple platelet function analyser; Roche Diagnostics AG). Results: Among 246 patients included, 142 were discharged on a new statin therapy or with an increase in previous dose (Inc-S), while 104 were already receiving a high-dose statin at admission, that remained unchanged (Eq-S). Median follow-up was 75.5 days. Patients in the Inc-S group were younger (p = 0.01), smokers (p < 0.001), with a less frequent history of hypercholesterolemia (p = 0.05), diabetes (p = 0.03), hypertension (p = 0.02), or previous cardiovascular events (p < 0.001). They were more often admitted for an acute coronary syndrome (p < 0.001) and used less anti-hypertensive drugs or nitrates. Higher total circulating calcium was observed in the Inc-S group (p = 0.004), while baseline vitamin D levels were similar in the 2 groups (p = 0.30). A significant reduction in the circulating low-density lipoprotein (LDL) cholesterol was observed in the Inc-S group. Vitamin D levels increased in the Inc-S patients but not in the Eq-S group (delta-25OHD: 23.2 ± 20.5% vs 3.1 ± 4.7%, p = 0.003), with a linear relationship between the magnitude of vitamin D elevation and the reduction of LDL cholesterol (r = − 0.17, p = 0.01). Platelet reactivity was significantly lower in the Inc-S patients, when evaluating aggregation with different platelet activating stimuli (arachidonic acid, p = 0.02, collagen, p = 0.004, thrombin-activating peptide, p = 0.07, ADP, p = 0.002). Conclusions: In patients with coronary artery disease, the addition of a high-intensity statin treatment, besides the lipid-lowering effects, is associated to a significant increase in vitamin D levels and lower platelet reactivity, potentially providing explanation of the "pleiotropic" benefits of statins therapy in cardiovascular disease. Highlights: Cardioprotective pleiotropic effects of statins are yet undefined Vitamin D displays antinflammatory and antithrombotic properties potentially mediating the anti-atherogenic benefits of statins We describe how the addition of a high-intensity statin provided a vitamin D raise in 246 patients with coronary artery disease Patients displaying the largest increase in vitamin D with statins showed a higher platelet inhibition on dual antiplatelet therapy.